Young People, Social Media and Health - Goodyear, Victoria A.; Armour, Kathleen M. (Routledge Studies in Physical Education and Youth Sport, 2019)
The pervasiveness of social media in young people's lives is widely acknowledged, yet there is little evidence-based understanding of the impacts of social media on young people's health and wellbeing. Young People, Social Media and Health draws on novel research to understand, explain, and illustrate young people's experiences of engagement with health-related social media; as well as the impacts they report on their health, wellbeing, and physical activity. Using empirical case studies, digital representations, and evidence from multi-sector and interdisciplinary stakeholders and academics, this volume identifies the opportunities and risk-related impacts of social media. Offering new theoretical insights and practical guidelines for educators, practitioners, parents/guardians, and policy makers; Young People, Social Media and Health will also appeal to students and researchers interested in fields such as Sociology of Sport, Youth Sports Development, Secondary Physical Education, and Media Effects.